Decision Analysis Of Debt Payment Obligations Number 270/Pdt.Sus-Pkpu/2019/Pn.Niaga.Jkt.Pst Regarding Legal Attempt To Fulfill The Rights Of Workers/Labors - Muhammad Hafidz (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
Decisions towards industrial relations disputes which have permanent legal force and certainty in its implementation are expected to guarantee justice for the parties, especially workers/labors. However, in practice, it is not easy to execute a decision that has permanent legal force, encouraging workers/labors to use the bankruptcy institution as an effort to obtain payment for their rights that have been regulated in the provisions of the legislation. This study aims to analyze the decision for debt payment obligation postponement of the Commercial Court at the Central Jakarta District Court Number 270/Pdt.Sus-PKPU/2019/PN.Niaga/Jkt.Pst related to legal attempt to fulfill workers' rights. According to the results of this paper, it can be seen that the court's decision which has permanent legal force punishing employers to pay for the rights of workers/labors is a debt in a broad sense. Industrial relations court decisions which have permanent legal force but cannot be implemented can be submitted as the basis for a request for suspension of obligation to pay debts. In this case, the court refers to the definition of debt in a broad sense, the debt has matured, the existence of two or more creditors, and the application of simple evidence.